Piezoelectric energy harvester composite under dynamic bending with implementation to aircraft wingbox structure. (1st October 2016) - Akbar, M.; Curiel-Sosa, J.L.
Abstract: In this paper, an investigation on the energy harvesting exerted by the dynamic bending responses of a piezoelectric embedded wingbox is presented. An innovative hybrid mathematical/computational scheme is built to evaluate the energy harvested by a mechanical system. The governing voltage differential equations of the piezoelectric composite beam are coupled with the finite element method output. The scheme is able of evaluating various excitation forms including dynamic force and base excitation. Thus, it provides the capability to analyse a complicated structure with a more realistic loading scenario. Application to the simulation of a notional jet aircraft wingbox with a piezoelectric skin layer is shown in some detail. The results pointed out that the electrical power generated can be as much as 25.24 kW for a 14.5 m wingspan. The capabilities and robustness of the scheme are shown by comparison with results from the literature.